ASSOCIATION BETWEEN PARIETAL LOBE VOLUME AND KOEDAM SCORE ON MRI IN PATIENTS WITH DEMENTIA (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the association between parietal lobe volume and the Koedam visual rating scale on brain MRI in patients with dementia. Methods: A cross-sectional study was conducted on 20 patients with dementia who underwent brain MRI using 3D T1-weighted sequences. Parietal lobe volumes were measured using a semi-automated segmentation method. Group comparisons were performed using independent-samples t-tests, and associations between parietal volumes, age, Koedam scores, and MMSE were assessed using Spearman correlation coefficients (p < 0.05). Results: The mean left parietal lobe volume was slightly higher than the right (88.51 ± 12.26 vs. 86.01 ± 11.22 cm³). Volumes were higher in males, with a significant difference in the left hemisphere (p < 0.05). Age showed a moderate negative correlation with left parietal volume (r = -0.484, p = 0.030). Notably, a strong inverse correlation was observed between the Koedam score and parietal lobe volumes bilaterally (r = -0.619, p = 0.004). No significant association was found between MMSE scores and parietal lobe volumes. Conclusion: Parietal lobe volume shows a significant inverse association with the Koedam score, supporting the consistency between qualitative and quantitative MRI assessments. These findings suggest that volumetric analysis may complement visual rating scales in the evaluation of dementia.
Keywords: Dementia; MRI volumetry; parietal lobe; Koedam score; brain atrophy.